Multimodal Endoscopic Assessment Guides Treatment Decisions for Rectal Early Neoplastic Tumors. Issue 3 (March 2020) - Emmanuel, Andrew; Lapa, Christo; Ghosh, Anil; Gulati, Shraddha; Burt, Margaret; Hayee, Bu'Hussain; Haji, Amyn
Abstract : BACKGROUND: There is a trend toward organ conservation in the management of rectal tumors. However, there is no consensus on standardized investigations to guide treatment. OBJECTIVE: We report the value of multimodal endoscopic assessment (white light, magnification chromoendoscopy and narrow band imaging, selected colonoscopic ultrasound) for rectal early neoplastic tumors to inform treatment decisions. DESIGN: This was a retrospective study. SETTING: The study was conducted in a tertiary referral unit for interventional endoscopy and early colorectal cancer. PATIENTS: A total of 296 patients referred with rectal early neoplastic tumors were assessed using standardized multimodal endoscopic assessment and classified according to risk of harboring invasive cancer. MAIN OUTCOME MEASURES: Sensitivity, specificity, positive and negative predictive values of multimodal endoscopic assessment, and previous biopsy to predict invasive cancer were calculated and treatment outcomes reported. RESULTS: After multimodal endoscopic assessment, lesions were classified as invasive cancer, at least deep submucosal invasion (n = 65); invasive cancer, superficial submucosal invasion or high risk of covert cancer (n = 119); or low risk of covert cancer (n = 112). Sensitivity, specificity, positive predictive values, and negative predictive values of multimodal endoscopic assessment for diagnosing invasive cancer, deep submucosal invasion, were 77%, 98%, 93%, and 93%. The combined classification of all lesions with invasive cancer or high risk of covert cancer had a negative predictive value of 96% for invasive cancer on final histopathology. Sensitivity of previous biopsy was 37%. A total of 47 patients underwent radical surgery and 33 transanal endoscopic microsurgery. No patients without invasive cancer were subjected to radical surgery; 222 patients initially underwent endoscopic resection. Of the 203 without deep submucosal invasion, 95% avoided surgery and were free from recurrence at last follow-up. LIMITATIONS: This was a retrospective study from a tertiary referral unit. CONCLUSIONS: Standardized multimodal endoscopic assessment guides rational treatment decisions for rectal tumors resulting in organ-conserving treatment for all patients without deep submucosal invasive cancer. See Video Abstract at http://links.lww.com/DCR/B133 . LA EVALUACIÓN ENDOSCÓPICA MULTIMODAL COMO GUÍA DE DECISIONES EN EL TRATAMIENTO DE TUMORES RECTALES NEOPLÁSICOS PRECOCES: ANTECEDENTES: La tendencia actual es la preservación del órgano en el manejo de los tumores de rectao. Sin embargo, no hay consenso sobre las investigaciones estandar para guiar dicho tratamiento. OBJETIVOS: Presentamos los valores de la evaluación endoscópica multimodal (luz blanca, cromoendoscopia de aumento, imagen de banda estrecha y ecografía colonoscópica seleccionada) para tumores rectales neoplásicos tempranos y así notificar las decisiones sobre el tratamiento. DISEÑO: Estudio retrospectivo. AMBIENTE: El estudio se realizó en una unidad de referencia terciaria para endoscopia intervencionista y cáncer colorrectal temprano. PACIENTES: Se evaluaron 296 pacientes referidos con tumores neoplásicos precoces de recto mediante una evaluación endoscópica multimodal estandarizada y se clasificaron de acuerdo al riesgo de albergar un cáncer invasivo. PRINCIPALES RESULTADOS: Se calcularon la sensibilidad, la especificidad, los valores predictivos positivos y negativos de la evaluación endoscópica multimodal y la biopsia previa para predecir el cáncer invasivo y se notificaron los resultados para el tratamiento. RESULTADOS: Después de la evaluación endoscópica multimodal, las lesiones se clasificaron como: cáncer invasive (al menos invasión submucosa profunda n = 65); cáncer invasive (invasión submucosa superficial o alto riesgo de cáncer encubierto n = 119) y finalmente aquellos de bajo riesgo de cáncer encubierto (n = 112). La sensibilidad, la especificidad, los valores predictivos positivos y negativos de la evaluación endoscópica multimodal para el diagnóstico de cáncer invasivo, la invasión submucosa profunda fueron 77%, 98%, 93% y 93% respectivamente. La clasificación combinada de todas las lesiones con cáncer invasivo o de alto riesgo de cáncer encubierto tuvo un VPN del 96% para el cáncer invasivo en la histopatología final. La sensibilidad fué de 37% en todas las biopsias previas. 47 pacientes fueron sometidos a cirugía radical, 33 por microcirugía endoscópica transanal. Ningún paciente sin cáncer invasivo fue sometido a cirugía radical. Inicialmente, 222 pacientes fueron sometidos a resección endoscópica. De los 203 sin invasión submucosa profunda, el 95% evitó la cirugía y no tuvieron recurrencia en el último seguimiento. LIMITACIONES: Estudio retrospectivo de una unidad de referencia terciaria. CONCLUSIÓN: La evaluación endoscópica multimodal estandarizada guía las decisiones racionales de tratamiento para los tumores rectales que resultan en un tratamiento conservador de órganos para todos los pacientes sin cáncer invasivo submucoso profundo. Consulte Video Resumen en http://links.lww.com/DCR/B133 .